(untitled) (Italian Journal of Public Health, 2005)
In order to evaluate the presence of Salmonella spp. in ready-to-eat foods, sixty-nine samples were analyzed using the BAXR system for Screening/Salmonella, a quick method based on PCR technology, and conventional culture procedures. Both methods showed the absence of Salmonella spp. in all samples and positive results for one sample artificially contaminated by a strain of Salmonella enteritidis, showing a full agreement. The biomolecolar system adopted appeared to be useful to supplement existing tests for the final identification of rough presumptive Salmonella isolates, for the rapid screening of food samples and the quick identification of Salmonella spp.